(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To review the treatment results of pediatric pneumonia patients using vancomycin and find out some its related factors. Subjects and methods: Descriptive study of 129 pediatric patients were diagnosed with pneumonia using treatment vancomycin at the Obstetrics and Pediatrics Hospital from April 2023 to March 2014. Results: The percentage of patients cured and improved after treatment was high, accounted for 58.9% and 28.7%, respectively. The death rate was low (1.6%). The median treatment period was 14 days. The mean initial maintenance vancomycin dose was 59.5 ± 2.3 mg/kg/day with dosing intervals every 8 hours in most pediatric patients in the study (89.9%). The median duration of vancomycin treatment was 10 (7-13) days. The rate of achieving the AUC target (400 - 600 mg.h/L) in the first dosing was 67.4%. Adverse events during vancomycin infusion accounted for 10.3%. Factors associated with an increased risk of subtherapeutic AUC at first measurement include: age > 24 months, increased renal clearance, and shock. Conclusion: It is necessary to optimize the initial dose of vancomycin in the population of pneumonia pediatric patients using vancomycin based on monitoring blood drug concentrations according to AUC taking into account factors such as age, renal clearance, and shock.